Cellular and molecular specificity of pituitary gland physiology - Perez Castro, Carolina Ines (2012)
The anterior pituitary gland has the ability to respond to complex signals derived from central and peripheral systems. Perception of these signals and their integration are mediated by cell interactions and cross-talk of multiple signaling transduction pathways and transcriptional regulatory networks that cooperate for hormone secretion, cell plasticity, and ultimately specific pituitary responses that are essential for an appropriate physiological response. We discuss the physiopathological and molecular mechanisms related to this integrative regulatory system of the anterior pituitary gland and how it contributes to modulate the gland functions and impacts on body homeostasis.